1 3 sin ( 2 ) + 2 3 sin ( 2 2 ) + 3 3 sin ( 3 2 ) + ⋯ = a b 1 + a b π b − b π
The expression above holds true for two positive integers a and b . Find 2 b + a .
The problem is original
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Is the first step a generalized summation formula?
Problem Loading...
Note Loading...
Set Loading...
Let's generalise the sum . The sum is in a form of n = 1 ∑ ∞ n 3 sin ( n θ )
Generally , n = 1 ∑ ∞ n sin ( n θ ) = 2 i 1 n = 1 ∑ ∞ n e i n θ − e − i n θ = − 2 i 1 ( lo g ( 1 − e i θ ) − lo g ( 1 − e − i θ ) ) = 2 i 1 lo g ( − e − i θ ) = 2 i lo g ( e i π ) − lo g ( e i θ ) = 2 π − θ Now integrate both sides from 0 to θ n = 1 ∑ ∞ ∫ 0 θ n sin ( n θ ) d θ = ∫ 0 θ 2 π − θ d θ n = 1 ∑ ∞ n 2 cos ( n θ ) = 4 θ 2 − 2 π θ + n = 1 ∑ ∞ n 2 1 Same process again you will get n = 1 ∑ ∞ n 3 sin ( n θ ) = 1 2 θ 3 − 4 π θ 2 + θ n = 1 ∑ ∞ n 2 1 = 1 2 θ 3 − 4 π θ 2 + 6 π 2 θ Put x = 2 You will get 1 3 sin ( 2 ) + 2 3 sin ( 2 2 ) + 3 3 sin ( 3 2 ) + ⋯ = 3 2 1 + 3 2 π 2 − 2 π Answer is 2 b + a = 7